The Ripple Effect of Giving: How Youth Food Sharing Fosters Social Happiness and Capability - Muhammad Sifa Fauzi Yulianis; Amir Bandar Abdul Majid Amir; Mohammad Suud; Salwa Abidah Zulfa; Gandes Hutami Ilmi; Vira Salsabella Anggraini; Robitul Huda; Nabila Meisya Fitri; Dio Fikri (TAAWUN, 2026)
The food-sharing activity aims to analyze the impact of youth-based Community Service initiatives on the social welfare and collective happiness of urban communities in Surabaya, amid ongoing food insecurity despite a declining trend in poverty rates. This study employs a Participatory Community Engagement approach, positioning youth and beneficiary communities as active actors in the design, implementation, and reflection on social intervention programs. The analysis is developed by integrating social capital theory and a capability approach. The results of this study demonstrate two intertwined layers of impact. At the community level, food sharing not only helps meet basic nutritional needs but also enhances psychosocial well-being by strengthening a sense of security, social recognition, and inclusion among informal workers and economically vulnerable households. At the youth level, involvement in the Community Empowerment Program has been shown to strengthen social skills, empathy, a sense of purpose, and emotional well-being. These findings confirm that youth-driven food-sharing initiatives extend beyond charitable practices and function as participatory social interventions that strengthen social cohesion and community capacity. This study makes an original contribution by conceptualizing youth-based community services as a potentially scalable participatory service model, with strategic implications for urban social resilience policy and for research on prosociality, happiness, and community development.